1984
DOI: 10.3109/00207458409089810
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical Activity and Related Phenomena Associated with Meditation Practice: A Literature Review

Abstract: The state effects of meditation appear to include decreased electrocortical arousal. There is also evidence that meditators more readily demonstrate alpha and theta activity than nonmeditators, even when not meditating. It is not clear whether prospective meditators as a group already possessed this characteristic, or whether the state effects of meditation practice eventually generalize to become traits. However, certain individuals, namely the psychologically "healthy" and those with a capacity for relaxed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 43 publications
4
34
0
1
Order By: Relevance
“…It was also reported that certain individuals, namely the psychologically 'healthy' and those with a capacity for relaxed absorbed attention, appeared to be more favorably disposed to meditation [26]. However, it is not clear whether prospective meditators as a group already possessed these characteristics, or whether the state effects of meditation practice eventually generalize to become traits.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that certain individuals, namely the psychologically 'healthy' and those with a capacity for relaxed absorbed attention, appeared to be more favorably disposed to meditation [26]. However, it is not clear whether prospective meditators as a group already possessed these characteristics, or whether the state effects of meditation practice eventually generalize to become traits.…”
Section: Discussionmentioning
confidence: 99%
“…For example 23) , a previous study compared three styles of yoga asana practice: the yoga posture, breathing exercises, and relaxation or resting posture. Some studies have reported that the heart rate decreases during meditation and while performing other meditation techniques 24,25) . Nonetheless, long time practitioners of meditation have been shown to have a marked decrease in heart rate 25,26) .…”
Section: Introductionmentioning
confidence: 99%
“…The research on the CNS effects of the RR that has been done suggests that the RR results in reductions in CNS arousal as measured by increases in alpha or theta EEG activity (Delmonte, 1984;West, 1980). However, this research has been hampered by a number of methodological problems, including lack of empirically sound experimental designs (self-selection bias, nonrandom assignment, no pretesting prior to training), reliance on visual analyses of a few channels of EEG activity, and failure to assess CNS effects in novice subjects to determine if the CNS effects of the RR are immediate.…”
mentioning
confidence: 99%